Tetraploids do not form cushions: association of ploidy level, growth form and ecology in the High Arctic Saxifraga oppositifolia L. s. lat. (Saxifragaceae) in Svalbard - Eidesen, Pernille Bronken; Müller, Eike; Lettner, Christian; Alsos, Inger Greve; Bender, Morgan; Kristiansen, Martin; Peeters, Bart; Postma, Froukje; Verweij, Koen Frans (Polar Research, 2013)
Saxifraga oppositifolia L. is a common circumpolar plant species that displays considerable morphological and genetic variation throughout its range. It is mainly diploid, but tetraploids are reported from several regions. The growth form varies from prostate to cushion-shaped, and the plant thrives in wet snow beds as well as on dry ridges. This variation has triggered the curiosity of many researchers, but as yet, no one has explained the observed morphological variation using ecological and/or genetic factors. However, the ploidy level has rarely been taken into account. This is the first study that demonstrates a significant correlation between ploidy level, ecology and growth form in S. oppositifolia. We successfully analysed 193 individuals of S. oppositifolia from 15 locations in Svalbard to investigate possible relationships among growth forms (prostrate, intermediate and cushion), ecological factors (vegetation and soil characteristics) and ploidy level. Results from flow cytometry reported 106 diploids, eight triploids and 79 tetraploids. Tetraploids almost exclusively showed prostrate growth, while the diploids displayed all three growth forms, evidence that growth form is at least partly genetically determined. Our analyses of environmental and vegetation data in relation to ploidy level indicated overlapping niches, but the tetraploids showed a narrower niche, and one shifted towards more benign habitats characterized by higher pH, higher soil temperatures and higher cover of vascular plants. The latter may suggest that tetraploids are slightly better competitors, but less hardy. Thus, autopolyploidy in S. oppositifolia has expanded the ecological amplitude of this species complex.